Comparison of water addition and early‐harvest strategies to decrease alcohol concentration in Vitis vinifera cv. Shiraz wine: impact on wine phenolics, tannin composition and colour properties. (22nd March 2020) - Teng, B.; Petrie, P.R.; Smith, P.A.; Bindon, K.A.
Abstract: Background and Aims: Regulations in some wine‐producing countries allow water addition to grape must. The research presented compared the impact of water addition to must on wine phenolics and colour relative to that of wines at the same alcohol concentration, prepared from fruit harvested earlier. Methods and Results: Shiraz grapes were harvested at three stages; earlier harvest at 13.4 and 14.4°Bé (H‐1, H‐2) and a later harvest at 15.6°Bé (H‐3). Water was then added to H‐3 must to match the sugar concentration of H‐1 and H‐2, respectively. Two modes of water addition were followed: (i) water was directly added to the must; or (ii) juice was substituted for water. Both water addition treatments significantly decreased the concentration of phenolics throughout the winemaking process. At the end of malolactic fermentation, the concentration of phenolics, tannin and non‐bleachable pigments, tannin molecular mass and wine colour density were lower in the water addition treatments compared with that of H‐3, but in all other compositional aspects were higher than that of H‐1 and H‐2. Interestingly, where the extent of alcohol reduction by water addition was equivalent, no difference in any of the measured wine attributes was found between the two modes of water addition. Conclusions: Water addition to the H‐3 treatment led to higher wine tannin, colour and non‐bleachable pigment than were found in wines made from grapes harvested at a lower sugar concentration. Significance of the Study: The study presents a meaningful comparison of potential outcomes in Shiraz wine phenolics and colour for producers who aim to lower alcohol using the approaches of either water addition or early harvest.